The Proper Meaning of “Proper”: Why the Regulation of Intrastate, Non-Commercial Species Under the Endangered Species Act Is an Invalid Exercise of the Commerce Clause - Kevin Simpson (Washington University Law Review, 2013)
This Note argues that the ESA‘s regulation of purely intrastate, non- commercial species is an invalid exercise of the Commerce Clause. Reviewing courts have reached the opposite conclusion via two doctrinal avenues: (1) by finding that the species in question bore "a substantial relation to interstate commerce" in satisfaction of the Court‘s framework set forth in United States v. Lopez, or (2) by holding that the species was an "essential part[] of a larger regulation of economic activity," an alternate path to Commerce Clause validity employed by the Court in its 2005 Gonzales v. Raich decision. Though these doctrines have the Court‘s approval, they do not flow from the commerce power alone. Because these approaches allow for regulation of objects or activities that merely affect interstate commerce, both implicitly rely on the classic constitutional catch-all: the Necessary and Proper Clause. This reliance requires that the regulation be both necessary for the achievement of a legitimate congressional purpose and constitutionally proper in its means of attaining it. Because the ESA‘s regulation of intrastate, non- commercial species impermissibly encroaches on areas of traditional state sovereignty, it is not constitutionally "proper," and is therefore unconstitutional.
Keywords: Endangered Species Act; ESA; Commerce Clause; Lopez; Gonzales; Raich